Potential Role of Cardiac Computed Tomography in Establishing Diagnosis of Ruptured sinus of Valsalva Aneurysm: Case Report (Ibrahim Cardiac Medical Journal, 2016)
Ruptured Valsalva aneurysm is a rare cardiac anomaly that may be congenital or acquired, a coexisting cardiac lesion might be present. The presentation may range from an asymptomatic murmur to cardiogenic shock. Most of these cases were earlier diagnosed using echocardiography and conventional angiography. But with the availability of advanced imaging modalities like cardiac CT this condition can be accurately assessed noninvasively. The high spatial resolution of cardiac CT provides anatomical details of the aneurysm by depicting a jet of contrast materials extending from the aneurysm and adjacent cardiac chamber. We report a case of ruptured aneurysm arising from the non-coronary sinus with a fistulous track connecting the sinus with the right atrium. This case was evaluated by 32 slice cardiac MDCT (Multi detector computed tomography) imaging. This was later confirmed peroperatively.Ibrahim Cardiac Med J 2014; 4(2): 64-67